Management of Bacterial Blight of Anthurium (Anthurium andreanum Linden) Using Botanicals - Sabitha S R (Department of Plant Pathology, College of Agriculture, 2002)
Anthurium (Anthurium andreanum Linden) suffers from a serIOUS disease viz., bacterial blight incited by Xanthomonas axonopodis pv. diefJenbachiae (McCulloch and Pirone) Vauterin et al. A survey was conducted in Thiruvananthapuram district and information on disease intensity and varietal reaction of the disease was studied from randomly selected thirty anthurium gardens. Plants with disease infection upto 50 per cent was noticed in most of the gardens. Generally pink varieties exhibited tolerance while red varieties were susceptible. Both foliar and systemic symptoms were observed. The bacterium was a gram negative, motile, short rod. Potato Sucrose Agar was the best solid medium for growth of the bacterium. Morphological, physiological and biochemical characters of the ten isolates were compared and some characters like nature and rate of growth, virulence and hydrolysis of starch were found varying. Aglaonema sp., Alocasia sanderiana, Anthurium ornatum, Colocasia esculenta, Dieffenbachia spp., Philodendron spp., Syngonium sp. and Xanthosoma sagittaefolium of Araceae family and ornamental plants like Orchid spp., Dracaena spp. Heliconia sp., Sterilitzia reginae and Maranta arundinaceae were hosts of the pathogen. Among the fifteen botanicals tested under in vitro conditions crude extract and 2 : 1 dilution of Allium sativum and Tagetes erecta, crude and two per cent concentration of neem cake extract and one and two per cent neem oil and coconut oil were 'effective in inhibiting the growth of the pathogen. The relative efficacy of five ecofriendly management practices viz., application of A. sativum, T. erecta, neem oil, coconut oil and neem cake